Additions to Distoseptispora (Distoseptisporaceae) associated with submerged decaying wood in China - Li, Wen-Li; Liu, Zuo-Peng; Zhang, Tian; Dissanayake, Asha J.; Luo, Zong-Long; Su, Hong-Yan; Liu, Jian-Kui (Phytotaxa, 2021)
In this study, three aquatic hyphomycetous taxa were collected and isolated from submerged wood in Lancang River located in the northwestern Yunnan Province, China. Phylogenetic analyses based on combined LSU, ITS, tef1-α and rpb2 sequence matrix indicated that these taxa belonged to Distoseptispora (Distoseptisporaceae), and they can be recognized as two new species Distoseptispora euseptata and D. yunnanensis. Two isolates of the new species Distoseptispora euseptata formed a distinct clade among Distoseptispora species (basal to D. suoluoensis and D. bambusae) with good support (ML 100%, MP 100%, BI 1.00 PP). Distoseptispora yunnanensis clustered together with D. euseptata, but they could be differentiated by the sizes of conidiophore and conidia. Corresponding illustrations, descriptions and phylogenetic evidences are provided to justify the placement of our newly collected Distoseptispora taxa.